The New Religious Political Right in Neo-Apartheid South Africa - Dube, Siphiwe Ignatius (Religion & theology, 2021)
This article argues that, in similar ways that scholars such as Kaye (1987) and Apple (1990) have respectively demonstrated how post 1970s America and Britain fused the neo-liberal discourse of free markets with the neo-conservative Christian discourse of moral rightness to found a New Right, we can apply this analytical model in post-apartheid/neo-apartheid South Africa. The aim of this analytical comparison is to support the broad claim that the article makes about the rise of the New Right in contemporary South Africa as directly related to the fusion of neo-Pentecostal Christianity with neoliberal economics in very salient ways. Using discourse analysis, the article demonstrates how the New Right in South Africa also draws from the language of crisis to justify a response that brings together the interlocking of race, religion, and neoliberalism. The paper’s main argument is that, a different type of New Right is emerging in current day South Africa, one that is not simply the purview of whitenationalism, but has main appeal also within the black middle-class.